Condemnation and lyricism in three films: "Children of Paradise", "The perfect circle" and "Before the rain" - Blanco de la Lama, Asunción (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
There are many films from the so-called independent cinema that denounce the age of globalization, consumerism, the irrationality of the irritating nationalisms, the predominant role of mass media, xenophobia. I had to restrict myself to three films that due to their similarities helped me to study the linguistic film signs, whose semantic constituents aim to condemn these aspects that are part of the so-called age of globalization. The denunciation is not made from the ideological commitment but from the ethical commitment, as the only way towards historical regeneration.The epic and lyrical structure of these films, similar to the Castilian ballad, focuses on the existencial hero facins people’s bad fate. All the narrative elements – language, structura, point of view– are directed towards the historical determinism of the characters, towards the denunciation of the historical drama of the under-developed countries, and towards nihilism from a philosophical point of view. In front of this ideological denunciation, which is part of the epic existence, the ethical commitment of the characters appears, maybe from the director himself, and which gives the lyrical character to the text. The solidarity among each other rescues mankind from the moral poverty in which he is immersed from centuries of fratricidal fight and from poverty facing the so-called consumer society, which only knows this situation from mass media.